Taglines: That's Saying a Lot - Young, Tara (Rural Telecommunications, 2019)
Rural telecommunications providers have a legacy of exceeding the needs of their constituencies- bringing telephone service to rural areas, being early adopters of dial up internet service, and linking rural communities to the rest of the world with broadband. [...]we went a different direction, renaming all of our products to what they actually were (HTC High-Speed Internet, HTC Digital Cable, etc.) while reinforcing the overall message of connection, and our ability to previde multiple services, with our tagline." MANAGING THE PROCESS One thing all companies stressed during the tagline development and rebranding process was securing buy-in from key constituent groups (corporate leadership, governing boards, employees), and communicating to the point of nearly over-communicating.